(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
The problem of gallstone disease, despite the current level of health care development, remains mainly a surgical problem, although a number of clinical situations require an integrated solution involving therapists, endoscopists, radiologists and doctors of other specialties. The study included 611 patients with gallstone disease complicated by mechanical jaundice, who, according to indications, underwent endoscopic retrograde cholangiopancreatography and endoscopic interventions. At the time of admission to the clinic, 174 patients had no mechanical jaundice, while 144 patients had a history of intermittent mechanical jaundice, and 30 patients had choledocholithiasis or choledoch ectasia on ultrasound. Being a minimally invasive intervention, endoscopic manipulations belong to the primary priority methods of diagnosis and treatment of patients with obstructive jaundice, however, despite their high diagnostic and therapeutic effectiveness, a rational approach is needed, taking into account the likely risk factors for the development of complications specific to this type of intervention.